2021
DOI: 10.3390/v13050760
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Porcine Pestiviruses: Relationships and Conserved Structural Features

Abstract: For two decades, the genus pestivirus has been expanding and the host range now extends to rodents, bats and marine mammals. In this review, we focus on one of the most diverse pestiviruses, atypical porcine pestivirus or pestivirus K, comparing its special traits to what is already known at the structural and functional level from other pestiviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 107 publications
(144 reference statements)
0
6
0
9
Order By: Relevance
“…It has been shown that viruses carrying a monomeric E rns were attenuated in vivo [62], but their replication was not affected in vitro [63]. In contrast to previous interpretations [64], two of the pestiviruses isolated so far, i.e., APPV and Bat pestiviruses, naturally lack homodimeric E rns based on the absence of the ninth cysteine. In our enzymatic assays, the E rns of these two viruses were not performing particularly differently from the other E rns proteins.…”
Section: E Rns Dimerizationmentioning
confidence: 78%
“…It has been shown that viruses carrying a monomeric E rns were attenuated in vivo [62], but their replication was not affected in vitro [63]. In contrast to previous interpretations [64], two of the pestiviruses isolated so far, i.e., APPV and Bat pestiviruses, naturally lack homodimeric E rns based on the absence of the ninth cysteine. In our enzymatic assays, the E rns of these two viruses were not performing particularly differently from the other E rns proteins.…”
Section: E Rns Dimerizationmentioning
confidence: 78%
“…Genetic sequencing of the DNA in the samples demonstrated the presence of Pestiviruses Aydin/04 and Burdur/05 , which were new variants of BDV [ 10 ]. There has been recorded evidence of cross-reactivity between other pestiviruses of importance to livestock, including BDV and APP, rendering diagnosis a challenge [ 33 , 34 ]. Cross-reactivity between BDV and BVDV has been reported to be a potential impediment in surveillance and diagnosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, an experimental inoculation study conducted in pregnant sows demonstrated that APPV was associated with congenital tremor (CT) type A-II in newborn pigs (Arruda et al, 2016). So far, APPV-associated CT has been reported in multiple continents, including Europe, America, and Asia (Riedel et al, 2021). Due to the lack of proofreading exonuclease activity of RNA polymerase, APPV strains worldwide have genetically high sequence variability (Postel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of proofreading exonuclease activity of RNA polymerase, APPV strains worldwide have genetically high sequence variability (Postel et al, 2017). Unsurprisingly, the highest diversity of APPVs to date was detected in China, which is an important pig-raising and pig-trading country (Riedel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation